PARADOXES IN POLICY IMPLEMENTATION: State Defense Program Anomaly - Toa, Akhmad Juni; Maarif, Samsul; Hidayat, Rachmat (Universitas Muhammadiyah Jember, 2020)
ABSTRACTThis paper carries out an in-depth review of the implementation of state defense policies in Situbondo so far which is still not optimal. To conduct in-depth research in this paper the researcher uses qualitative research with a porposive approach in order to obtain valid, in-depth and proportional information. The results of the study concluded that: First, the implementation of state defense policy in Situbondo Regency is still not optimal in achieving its stated goals, because there is a paradox in its implementation. This paradox arises because in the implementation of state defense policies top down and ignores local potential, such as the role of charismatic kiai - social capital - which has a strong influence in the Situbondo community so far, so that it has a direct impact on the creation of regional stability, as one of the objectives of national defense. Secondly, because there is a paradox in the implementation of the country's defense policy, it eventually gave birth to an anomaly in the National Defense Program because the Ministry of Defense on one hand wanted the birth of as many national defense cadres, in order to maintain the country's existence from various threats. But on the other hand, in its implementation the Ministry of Defense is exclusive by ignoring the role of the kiai as a very important social capital in the area in encouraging the optimization of the State Defender Program in Situbondo.